THE DEVELOPMENT OF FUTURE TEACHERS’ METHODOLOGICAL COMPETENCE IN PRIMARY SCHOOL WHEN LEARNING INTEGRATED COURSES IN THE NETWORK COMMUNITIES - Sergeeva, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The purpose of the article is to describe a study of the possibilities of network communities for the development of students' methodological competence in studying integrated courses. The article substantiates the advantages of using the integrated approach for the formation future primary school teachers’ methodological competence. It’s revealed the didactic potential of network communities in the formation and development of students' methodological competence. There are tools and methods that ensure the development of the methodological competence in the integrated courses study. The research allowed establishing the positive impact of the selected methods and tools implementation when studying integrated courses using the network communities to develop students' methodological competence.